Epigenetic Silencing of STAT3-Targeted miR-193a, by Constitutive Activation of JAK/STAT Signaling, Leads to Tumor Progression Through Overexpression of YWHAZ in Gastric Cancer - Wei, Kuo-Liang; Chou, Jian-Liang; Chen, Yin-Chen; Low, Jie-Ting; Lin, Guan-Ling; Liu, Jing-Lan; Chang, Te-Sheng; Chen, Wei-Ming; Hsieh, Yung-Yu; Yan, Pearlly S.; Chuang, Yu-Ming; Lin, Jora M. J.; et al. (Frontiers in Oncology, 2021)
Purpose The purpose of this study was to identify genes that were epigenetically silenced by STAT3 in gastric cancer. Methods MBDcap-Seq and expression microarray were performed to identify genes that were epigenetically silenced in AGS gastric cancer cell lines depleted of STAT3. Cell lines and animal experiments were performed to investigate proliferation and metastasis of miR-193a and YWHAZ in gastric cancer cell lines. Bisulfite pyrosequencing and tissue microarray were performed to investigate the promoter methylation of miR-193a and expression of STAT3, YWHAZ in patients with gastritis (n = 8) and gastric cancer (n = 71). Quantitative methylation-specific PCR was performed to examine miR-193a promoter methylation in cell-free DNA of serum samples in gastric cancer patients (n = 19). Results As compared with parental cells, depletion of STAT3 resulted in demethylation of a putative STAT3 target, miR-193a, in AGS gastric cancer cells. Although bisulfite pyrosequencing and epigenetic treatment confirmed that miR-193a was epigenetically silenced in gastric cancer cell lines, ChIP-PCR found that it may be indirectly affected by STAT3. Ectopic expression of miR-193a in AGS cells inhibited proliferation and migration of gastric cancer cells. Further expression microarray and bioinformatics analysis identified YWHAZ as one of the target of miR-193a in AGS gastric cancer cells, such that depletion of YWHAZ reduced migration in AGS cells, while its overexpression increased invasion in MKN45 cells in vitro and in vivo. Clinically, bisulfite pyrosequencing revealed that promoter methylation of miR-193a was significantly higher in human gastric cancer tissues (n = 11) as compared to gastritis (n = 8, p < 0.05). Patients infected with H. pylori showed a significantly higher miR-193a methylation than those without H. pylori infection (p < 0.05). Tissue microarray also showed a positive trend between STAT3 and YWHAZ expression in gastric cancer patients (n = 60). Patients with serum miR-193a methylation was associated with shorter overall survival than those without methylation (p < 0.05). Conclusions Constitutive activation of JAK/STAT signaling may confer epigenetic silencing of the STAT3 indirect target and tumor suppressor microRNA, miR-193a in gastric cancer. Transcriptional suppression of miR-193a may led to overexpression of YWHAZ resulting in tumor progression. Targeted inhibition of STAT3 may be a novel therapeutic strategy against gastric cancer.